Bytelearn - cat image with glassesAI tutor

Welcome to Bytelearn!

Let’s check out your problem:

4y4y24y2+1dy\int \frac{4y^{4}-y^{2}}{4y^{2}+1}\,dy

Full solution

Q. 4y4y24y2+1dy\int \frac{4y^{4}-y^{2}}{4y^{2}+1}\,dy
  1. Split Integrand: Simplify the integrand if possible.\newlineThe integrand (4y4y2)/(4y2+1)(4y^{4}-y^{2})/(4y^{2}+1) can be split into two separate fractions: 4y4/(4y2+1)y2/(4y2+1)4y^{4}/(4y^{2}+1) - y^{2}/(4y^{2}+1).
  2. Integrate First Term: Integrate the first term 4y4/(4y2+1)4y^{4}/(4y^{2}+1). Notice that the numerator is the derivative of the denominator. Therefore, the integral of 4y4/(4y2+1)4y^{4}/(4y^{2}+1) with respect to yy is simply the natural logarithm of the absolute value of the denominator. 4y4/(4y2+1)dy=ln4y2+1+C1\int 4y^{4}/(4y^{2}+1) dy = \ln|4y^{2}+1| + C_{1}, where C1C_{1} is an arbitrary constant.
  3. Integrate Second Term: Integrate the second term y24y2+1-\frac{y^{2}}{4y^{2}+1}. This term does not simplify directly, and it does not match a standard integral form. We can try a substitution or partial fractions, but in this case, partial fractions do not apply since the degree of the numerator is less than the degree of the denominator. We will attempt a substitution. Let u=4y2+1u = 4y^{2}+1, then du=8ydydu = 8y dy. We need to express y2dyy^{2} dy in terms of uu and dudu. Since u=4y2+1u = 4y^{2}+1, y2=u14y^{2} = \frac{u-1}{4}. Also, dy=du8ydy = \frac{du}{8y}.
  4. Substitute in Integral: Substitute y2y^{2} and dydy in terms of uu and dudu in the integral.\newlineWe have y2=u14y^{2} = \frac{u-1}{4} and dy=du8ydy = \frac{du}{8y}, so we can write:\newliney24y2+1dy=(u1)41udu8y\int -\frac{y^{2}}{4y^{2}+1} dy = \int -\frac{(u-1)}{4} \cdot \frac{1}{u} \cdot \frac{du}{8y}.\newlineHowever, we have a yy in the denominator of du8y\frac{du}{8y} which we have not expressed in terms of uu. This is a mistake because we cannot integrate with respect to uu while still having a variable yy in the expression.